1972
DOI: 10.1177/00220345720510062201
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic-Fetal Toxicity and Teratogenic Effects of a Group of Methacrylate Esters in Rats

Abstract: Monomers of five methacrylate esters and acrylic acid were administered at three dose levels to female rats on days 5, 10, and 15 of gestation. The incidences of resorptions, dead fetuses, gross abnormalities, and skeletal malformations are presented for each of these groups. Mean fetal weights also were determined for each group, and those of the monomer-treated groups were significantly smaller (P ---0.01) than those of the untreated controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 7 publications
1
46
0
Order By: Relevance
“…It has been reported that methyl methacrylate (MMA) may be teratogenic and can cause adverse cardiovascular effects in animals (Phillips et al, 1971, Singh et al, 1972Karlsson et al, 1995). In addition, subcutaneous polymethyl-methacrlylate implants induced malignant tumors in rodents (Oppenheimer et al, 1955).…”
Section: (G) Pulp Studies In Animals and Humansmentioning
confidence: 99%
“…It has been reported that methyl methacrylate (MMA) may be teratogenic and can cause adverse cardiovascular effects in animals (Phillips et al, 1971, Singh et al, 1972Karlsson et al, 1995). In addition, subcutaneous polymethyl-methacrlylate implants induced malignant tumors in rodents (Oppenheimer et al, 1955).…”
Section: (G) Pulp Studies In Animals and Humansmentioning
confidence: 99%
“…Lawrence and Autian (7) demonstrated that when animals were exposed to methyl methacrylate and ethyl methacrylate vapors, sleeping time (from administration of pentobarbital sodium) was extended. For example, exposure for 13 Treon and associates (4), in another study, repeatedly exposed animals (rats, rabbits, guinea pigs, and monkeys) to various concentrations of methyl and ethyl acrylate in air for periods of 7 hr. They recorded the concentration which did not kill any of the animals and the next higher concentration which did produce deaths.…”
Section: Introductionmentioning
confidence: 99%
“…Hence present evidence implies, but does not prove, that it is rather unlikely that methyl methacrylate metabolism would yield damaging reactive metabolites, since an acceptable pathway has been proposed which is independent of the microsomal and cytoplasmic enzymes that are usually concerned with foreign compound metabolism. The report of Singh et al (1972) is accordingly difficult to reconcile and, in practice, i.p. injection would niever be selected as the route for the testing of embryonal-foetal toxicity and teratogenicity per se (Hathway, 1975), since a compound under examination might be absorbed from the peritoneum into the foetuses direct, and not via the placenta.…”
Section: Methodsmentioning
confidence: 98%